2001
DOI: 10.1111/j.1744-6570.2001.tb00234.x
|View full text |Cite
|
Sign up to set email alerts
|

What Do Proactive People Do? A Longitudinal Model Linking Proactive Personality and Career Success

Abstract: We developed and tested a model linking proactive personality and career success through a set of four behavioral and cognitive mediators. A 2‐year longitudinal design with data from a sample of 180 full‐time employees and their supervisors was used. Results from structural equation modeling showed that proactive personality measured at Time 1 was positively related to innovation, political knowledge, and career initiative, but not voice; all measured at Time 2. Innovation, political knowledge, and career init… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

60
1,142
7
44

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 1,254 publications
(1,253 citation statements)
references
References 102 publications
60
1,142
7
44
Order By: Relevance
“…Some studies show that individuals high in extraversion report high levels of job satisfaction (Judge et al 2002;Sutin et al 2009). Some studies also show that individuals high in extraversion obtain more promotions (Seibert et al 2001), receive comparatively high incomes (Sutin et al 2009) and have shorter unemployment spells compared to individuals low in extraversion (Kanfer et al 2001). Extraversion means a tendency to seek stimulation and the company of others.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies show that individuals high in extraversion report high levels of job satisfaction (Judge et al 2002;Sutin et al 2009). Some studies also show that individuals high in extraversion obtain more promotions (Seibert et al 2001), receive comparatively high incomes (Sutin et al 2009) and have shorter unemployment spells compared to individuals low in extraversion (Kanfer et al 2001). Extraversion means a tendency to seek stimulation and the company of others.…”
Section: Discussionmentioning
confidence: 99%
“…Sutin et al (2009) find that emotionally stable as well as extrovert and conscientious individuals report higher income and higher job satisfaction. Seibert et al (2001) find that extrovert individuals obtain more promotions than non-extrovert individuals, whereas Nyhus and Pons (2005) find agreeableness to be negatively associated with income.…”
Section: Personality and Workmentioning
confidence: 98%
“…In a longitudinal study, proactive personality was positively related to innovation, political knowledge, and career initiative, all of which, in turn, had positive relationships with career progression and career satisfaction (Seibert, Kraimer, & Crant, 2001). Longitudinal socialization research showed that proactive personality predicted newcomers' reports of task mastery (Kammeyer-Mueller & Wanberg, 2003).…”
Section: Proactive Personalitymentioning
confidence: 95%
“…Such change-oriented behaviors likely increase their job control. Indeed, proactive people are reported to make positive work changes by making constructive suggestions (Parker & Collins, 2010), negotiating idiosyncratic deals (Hornung, Rousseau, & Glaser, 2008), and taking career initiatives (Seibert et al, 2001). A meta-analysis showed a corrected cross-sectional correlation of .28 between proactive personality and job control (Fuller & Marler, 2009).…”
Section: Proactive Personality and Changes In Work Characteristics: Smentioning
confidence: 99%